Money politics and the obstacles on national leadership succession - Suswantoro, Gunawan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
This paper reflects the succession of national leadership, especially at the level of regional leaders. The succession of the national leadership is currently facing various problems, including insufficient competencies, poor quality of regeneration from political parties, and the presence of many prospective leaders who suddenly enter during the election process. The problems in the regeneration of national leaders occur due to many factors. One of the most influential factors in the author's view is the rise of money politics in the Pilkada (Regional Simultaneous Election). Money politics is a severe obstacle in democratic life because it has proven successful in blocking the way for the regeneration of potential leaders—likewise, political parties are trapped in carrying candidates with "deep pockets" to finance party operations. Finally, money politics that has become entrenched has become the new normal by directing people to vote for candidates with the lure of material instead of the program to be carried out. Money politics, in some cases, refer to the Indonesian people's economic condition and education, which are still relatively low. In addition, direct local elections, held directly so far, have also added space for more fertile money politics. Therefore, this paper proposes a solution that can be taken to improve the current system. The author suggests implementing the Asymmetric Election System, which can carry out two alternative electoral systems. The alternative electoral system will be applied by looking at the parameters of democracy that will be measured in each region. Local elections can be run by direct elections for areas with a high parameter. On the other hand, in regions with low democratic parameters, local elections must be carried out with an indirect system. The proposed indirect Pilkada system is not the same as the indirect Pilkada during the New Order. There are some changes and improvements so that community participation becomes more accommodated. It is hoped that money politics can be eradicated with the proposed system, and the Pilkada can return to its function as a succession of national leadership in the regions.